Algeria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper develops a structural macroeconomic model for Algeria that can help inform the discussion of the policy choices faced by the authorities. The model captures the core dynamics of Algeria's macro-economy and provides an organizing framework for forecasting and policy analysis that can facilitate an assessment of the optimal policy responses to oil shocks and the implications for macroeconomic stability. This paper also examines Algeria's main subsidies and proposes reform strategies, drawing on cross-country experiences, and discusses the channels through which a prolonged period of low oil prices may affect the banking sector, together with the policies needed to mitigate emerging financial stability risks.